PELATIHAN PEMBUATAN LABEL KEMASAN PRODUK MENGGUNAKAN CORELDRAW BAGI SISWI SMK IBRAHIMY 1 SUKOREJO - Zaehol Fatah; Naila Ismi Fadila (Jurnal Padamu Negeri, 2026)
The rapid development of the creative industry has driven the demand for workers with graphic design skills, particularly in product packaging label creation. SMK Ibrahimy 1 Sukorejo, as a vocational education institution, is required to equip students with relevant and applicable competencies that meet industry needs. However, graphic design skills among students remain limited, both in terms of theoretical understanding and practical ability to operate design software. Therefore, this community service activity in the form of training on product packaging label creation using CorelDRAW application was conducted as an effort to enhance students' competencies in this field. The method employed was participatory training based on direct practice, conducted at the Computer Laboratory of SMK Ibrahimy 1 Sukorejo over one day with an effective duration of 3 hours. The training consisted of four stages: preparation, material presentation, independent practice, and evaluation. The material delivered included an introduction to the CorelDRAW interface, basic concepts of packaging label design, color and typography selection, as well as file export techniques for printing purposes. The assessment results of participants' design works showed an overall average score of 81.05, categorized as good, with the typography readability aspect achieving the highest score of 83.10. The participants' satisfaction level with the training implementation reached an average of 4.32 out of a 5-point scale, with the statement regarding the benefits of training achieving the highest score of 4.60. This training proved to be effective in improving students' graphic design skills and equipping them with competencies ready to be applied to support MSME development and work readiness in the creative industry sector.